Distribution of heavy metals and organic in the clam culture areas at Binh Dai, Ba Tri, Thach Phu in Ben Tre province - Dung, Le Trong; Thu, Nguyen Hong; Phu, Le Hung; Ngoc, Pham Hong; Ha, Dao Viet (Vietnam Journal of Marine Science and Technology, 2019)
The paper presents the contents of metals and organic in the surface sediments (5–10 cm) at the submerged clam culture areas in Ben Tre province. The metal samples were digested by nitric acid 10% and analyzed by ICP-MS method, total organic matters (HC) were determined by the burning method at 500oC. The results showed that the content of Zn ranged from 22.4 to 48.1 µg/g, Cu: 3.3–25.1 µg/g, Pb: 7.3–27.8 µg/g, As: 1.1–4.7 µg/g, Cd: 0.1–0.4 µg/g, Ni: 8.3–4.5 µg/g, Co: 7.3–11.9 µg/g, Cr: 5.8–15.3 µg/g, Fe: 0.8–1.74 µg/g and organic: 1.2–8.4%. The contents of all elements in the sediment in the canals were much higher than in the clam culture areas at the river mouths. The concentrations of metals in clam culture areas were lower than threshold effect levels (TEL) according to Canadian standards.